ANALISIS PENETAPAN TARIF AGEN BRI LINK BERDASARKAN PRINSIP AKUNTANSI SYARIAH DI KELURAHAN LABUHAN BILIK KEC. PANAI TENGAH, KAB LABUHAN BATU - Saidah Mayasari Tanjung; Amsah Hendri Doni (Jurnal Ekonomi dan Bisnis, 2025)
This study aims to analyze the determination of transfer withdrawal rates at BRI Link Agents in Panai Tengah District based on sharia accounting principles. The researcher chose this location because it is his home area and has sufficient understanding of the development of BRI Link there. There are five BRI Link agents in Panai Tengah Subdistrict, with rapid growth compared to other villages, as seen from the number of transactions that occur every month. However, there are significant rate differences between these agents in setting transaction fees, including transfer rates, which range from Rp3,000 to Rp5,000 depending on the amount of money transferred. The research method used is a descriptive qualitative approach, to understand and explain social phenomena related to BRI Link agent tariff setting. Through surveys and interviews with agents and customers, it was revealed that there is an independent tariff setting mechanism, which is not determined by Bank Rakyat Indonesia. BRI Link agents set tariffs based on costs incurred and distance from the bank, resulting in tariff variations between agents. Despite efforts to follow sharia accounting principles, there are still indications of fraud among agents in tariff setting that threaten the principles of fairness and transparency. The results show that BRILink agents play an important role in facilitating banking services in the community, but challenges related to fairness and integrity in tariff setting still need to be addressed. This research is expected to provide insights for the development of more equitable and sharia-compliant policies in banking services in the region.